HUMAN RESOURCE MANAGEMENT PRACTICES FOR EFFECTIVE ORGANIZATIONAL CHANGE : A REVIEW OF RESEARCH IN WESTERN AND NON-WESTERN COUNTRIES - Supratikta, Hadi; Rachman, Lindra; Fauziah, Sri (Journal of Industrial Engineering & Management Research, 2024)
The success of an organization or company depends on the performance of the employees produced, whether the performance of the employees produced is good or bad, good or not. Because employees are the driving force for a company itself. Employees who produce good performance will have a direct impact on the progress obtained by the company. Performance is a problem that is often discussed. employee performance or usually in other words employee performance is the work performance or achievement that a person achieves in a genuine way. With high employee performance, it can be a competitive advantage of the organization or company. If the company competes using human resources, the results that will be obtained are two, namely competitive advantage and comparative advantage, because the existence of this advantage will certainly make it difficult for competitors to imitate what we produce (Tohardi, ). Employee performance is the result of quality and quantity work produced by employees or also called behavior that is displayed in accordance with the responsibilities given to the employee himself (Murty and Hudiwirnasih,). Performance is also the result of work produced or given by an employee that is directly related to the duties and responsibilities given by the company (Mangkunegara,). Therefore, with good employee performance, it is hoped that the company will continue to provide appropriate motivation so that other companies can judge that the company has quality performance. Employee performance is closely related to the motivation that the organization applies or already exists in the company. The motivation provided in an organization is expected to help or have a good impact on its employees, especially in creating high performance. Companies that can apply and provide motivation according to the needs of their employees will certainly affect their work performance and performance. As for motivation as one of the important things that must be given to employees, the lack of motivation provided can have an impact on their performance, such as increased absenteeism and decreased employee involvement in doing their duties. Low employee morale can help the company's achievement to meet its goals take longer and disrupt the company's profitability. Therefore, companies must pay attention to the motivation of employees. Motivation is one of the important roles for human behavior and performance, from the level of motivation in individuals and teamwork in a person can affect all aspects of organizational performance. The total success of organizational projects depends on the commitment of the team, which depends directly on their level of motivation In the Hawthrone Study conducted by Elton Mayo in the year and, the need for employees to get higher job performance has been found not only in giving intensive money, but also shows that employees are influenced by external elements as well and how they can organize themselves in informal groups. The right motivation can encourage employees to do as much as possible in doing their duties, with high motivation encouraging individuals to commit to their work. Motivation is closely related to the attitudes and behavior of each individual, motivation itself can also be interpreted as a condition in a person's personality so that the person is encouraged or wants to carry out the desired activities and activities Motivation can be influenced by several aspects such as employee loyalty, life demands, targets to be achieved and other factors. Sometimes work motivation also has a negative effect on employees because of the motivation to compete to be the best employee in a way that is not good, such as damaging the character of the employee's coworkers. Therefore, high motivation affects the performance of the organization itself and also improves one's own performance including ability, expertise and ethics.Based on the description above, the researcher sees the importance of the Human Resources (HR) factor in supporting the practice of Effective Organizational Change so that workers or employees are ready for the Company's future challenges which involve changes to achieve the goals to be achieved.